PEMELIHARAAN ASET PEMERINTA H KABUPATEN KUANTAN SINGINGI DI LOKASI OBJEK WISATA AIR TERJUN GURUH GEMURAI TAHUN 2019 - Syamsi, Dadang Mario; ", Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Regional assets are all regional assets in the form of tangible and intangible goods. Regional assets are one of the important elements in the implementation of government and services to the community. Regional assets are important resources for local governments because regional assets or goods are the economic potentials owned by the regions. Kuantan Singingi Regency in the tourism sector has great potential to be explored. The wealth of tourism potential that is owned by Kuantan Singingi Regency, of course, requires good and appropriate management. To manage this potential, the main role is in the hands of local governments. However, the local government has not shown its seriousness in managing Kuantan Singingi tourism, this can be seen from the absence of regulations governing tourism development. This study aims to describe the maintenance of government assets of Kuatan Singingi Regency which is located in the location of the Guruh Gemurai Waterfall Tourism Object. In addition, to find out the factors that become obstacles to this implementation. This research uses descriptive qualitative methods and data collection techniques based on observation, literature study and interviews. The results of this study indicate that the maintenance of local government assets at the location of the Guruh Gemurai waterfall tourist attraction in 2019 consists of recording the plan for the needs of regional assets consisting of supervision and maintenance which is constrained by a limited budget. Inhibiting factors consist of internal factors and external factors. As for the internal factors that become obstacles, namely, limited funds, the absence of a Regional Regulation concerning the Master Plan for Regional Tourism Development, and inadequate Human Resources. Meanwhile, the external factor that becomes an obstacle is the low participation of the private sector in developing tourism destinations..Keywords: Regional Assets, Regional Asset Maintenance